Consumption Patterns and Returns in the US DVD market - Lee Yoong Hon; Ruth Lim Sheau Yen (Australasian Accounting, Business and Finance Journal, 2023)
We examine the ancillary revenue for movies, specifically its revenue from DVD sales. We compared the sales and returns to investment for DVD among different categories of DVD titles/movies based on their movie production budgets. We find that while bigger budget movies will sell more DVDs they performed poorer when it comes to returns to investment (R.O.I.). JEL classification: L80, L82, M20, M21.
Keywords: DVD; consumption pattern; home entertainment industry; returns to investment